Intercultural adjustment in high context communication: the mediating role of intercultural willingness to communicate on AUM theory - Huiwen, Sun; Hashim, Norliana; Sern, Tham Jen; Bidin, Rosmiza (Human Resource Management Academic Research Society, 2022)
Underpinned by anxiety/uncertainty management (AUM) theory, this study uses Baron and Kenny’s (1986) framework to test the prediction that intercultural willingness to communicate (IWTC) mediated the relationship between anxiety and uncertainty among international students at University Putra Malaysia. The previous study displayed a significant relationship between anxiety, uncertainty, and intercultural adjustment while moderated by mindfulness. As a high-context culture in communication, Malaysia specialized in interpersonal and intergroup communication among ethnic and races. While intercultural willingness to communicate plays a crucial role in intercultural communication. Results through Multi-linear regression (SPSS) to investigate a possible method for testing mediation effects of intercultural willingness to communicate (IWTC) on the relationship between anxiety and uncertainty. Employed surveys were used to collect data to test hypotheses predicting intercultural adaptation. A total of 201 international students which includes undergraduates and post-graduate students at the University Putra Malaysia participated in the survey. This study revealed that anxiety and uncertainty have a direct negative influence on intercultural willingness to communicate and an indirect negative influence on intercultural adjustment. Especially, this study was conducted under the effect of the Covid-19 pandemic.